A new spurless species of Impatiens sect. Microsepalae (Balsaminaceae) from south India - Prabhukumar, K.m.; Ashok, Reshma; Prakash, P.m. Binu; Balachandhran, Indira (Phytotaxa, 2023)
An interesting balsam with spurless lower sepal is described here as a new species to the Impatiens Sect. Microsepalae (Balsaminaceae) from southern parts of Western Ghats, India. Detailed notes on description, ecology, and distribution are provided along with a comparison of its morphologically similar species and colour photographs.